2008
DOI: 10.1002/app.27975
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultrasonic waves in activation of microcrystalline cellulose

Abstract: In this work, microcrystalline cellulose (MCC) was activated with ultrasonic waves. The influences of ultrasonic treatment on the changes of supramolecular structures and morphology structure were studied by WAXS and SEM. The accessibility of the MCC was characterized by water retention value (WRV) and specific surficial area. The influence of ultrasonic treatment on the reactivity of MCC was investigated through the reaction of MCC being oxidized into 2,3-diadehyde cellulose (DAC) by periodate sodium. The mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 9 publications
0
21
1
1
Order By: Relevance
“…In a study conducted by Wang et al [43], the degree of crystallinity of MCC after ultrasonic treatment negligibly decreased from 62% to 61%, when the ultrasonic power increased from 0 W to 200 W. However, with increasing ultrasonic power from 200 W to 700 W, a significant decrease in the degree of crystallinity of MCC was observed. It should be noted that although the degree of crystallinity decreased to 54.6% at 700 W for 15 min, the crystal size showed little change under this condition [43]. In another study it was found that both the degree and size of crystalline cellulose did not change so much after ultrasound treatment under 400 W for 12 min [37].…”
Section: Crystallinitymentioning
confidence: 94%
See 4 more Smart Citations
“…In a study conducted by Wang et al [43], the degree of crystallinity of MCC after ultrasonic treatment negligibly decreased from 62% to 61%, when the ultrasonic power increased from 0 W to 200 W. However, with increasing ultrasonic power from 200 W to 700 W, a significant decrease in the degree of crystallinity of MCC was observed. It should be noted that although the degree of crystallinity decreased to 54.6% at 700 W for 15 min, the crystal size showed little change under this condition [43]. In another study it was found that both the degree and size of crystalline cellulose did not change so much after ultrasound treatment under 400 W for 12 min [37].…”
Section: Crystallinitymentioning
confidence: 94%
“…It seems that the treatment time of cellulosic materials using low-power ultrasound irradiation does not significantly affect the crystallinity of cellulose [43]. Generally, there is no linear relation between crystallinity and treatment time in the different powers of ultrasound waves [37,43,44].…”
Section: Crystallinitymentioning
confidence: 97%
See 3 more Smart Citations